PENGARUH KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. ABADI LESTARI MANDIRI PALEMBANG - Nina Fitriana; Frecilia Nanda Melvina (Fakultas Ekonomi Universitas Tridinanti Palembang, 2021)
This study aims to determine the influence of communication and organizational culture on the performance of employees of PT. Abadi Lestari Mandiri Palembang, either partially or simultaneously.The method used is a descriptive method with multiple regression analysis. The population in this study were employees at PT. Abadi Lestari Mandiri Palembang, amounting to 45 people. The results of this study indicate that simultaneously communication and organizational culture have an influence on the performance of the employees of PT. Abadi Lestari Mandiri. Organizational culture variables have a dominant influence on the performance of PT. Abadi Lestari Mandiri Palembang with a value of 0.836%.